A New Era in the Implementation of Rehabilitation and Compensation Rulings in State Administrative Courts - Tri Cahya Indra Permana; Amiludin Amiludin (Journal of Law and Legal Reform, 2024)
The implementation of court rulings on rehabilitation and compensation in the State Administrative Court has entered a new era with the issuance of execution guidelines for the supervision of rulings with permanent legal force by the Head of the State Administrative Chamber of the Supreme Court of the Republic of Indonesia. These guidelines mark the first time in the history of the Supreme Court that a compensation amount has been reassessed and determined by the Serang State Administrative Court due to the failure to implement rehabilitation in an employment dispute. The compensation awarded does not refer to Government Regulation No. 43 of 1991, which limits compensation to between one hundred thousand rupiah and two million rupiah, but instead is based on the actual losses of the petitioner. This practice has set a positive precedent for the execution of compensation or monetary payments, which is expected to be followed by other State Administrative Courts. It is hoped that the Plaintiffs/Execution Applicants will follow the legal enforcement procedures outlined in the Minister of Finance Regulation Number 80/PMK.01/2015 regarding the Implementation of Legal Decisions, enabling the realization of compensation payments, and it is recommended that the Minister of Finance execute the legal decisions, especially the Supreme Court's re-determination regarding the compensation payment amount, so that justice for the Plaintiffs/Execution Applicants can be fully realized.